Teaching Writing in Blended Environment - Handoko Handoko; Ayumi Ayumi (JURNAL ARBITRER, 2021)
The article aims to describe the implementation blended learning environment in teaching writing skills. The research is based on the blended learning framework that integrates face-to-face methods and online learning methods. The face-to-face method is given to see students' activeness in delivering ideas and brainstorming before writing essays. The online learning method is used to see students' ability to elaborate ideas from drafting to become a complete essay. Thus, students can be effective in learning in class to discuss their draft an essay and not spend much time writing. The implementation of blended learning was distributed to three session: brainstorming, drafting, and final writing. The evaluation was done for each cycle. After the evaluation, students get feedback for their performance in the previous session. The result post-test shows that students in the experimental class have indicated a significant improvement in essay writing performance with significance 0,06>0,05 with an average score of 76,35. The result of the research is very important as a framework to develop learning models for teaching writing at universities.